2022
DOI: 10.1007/s10668-022-02168-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk management in green building: a review of the current state of research and future directions

Abstract: There has been considerable interest in investigating risk factors in Green Building (GB) projects, with increasing debates in recent years. This study aims to investigate tendencies and identify gaps in the GB risk literature, which can define future research guidelines, with an extensive analysis of the latest contributions. A systematic literature review was conducted by analyzing 64 relevant studies from 2006 to 2020. The results revealed that the GB risk topic is somewhat nascent but growing and almost li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…In addition to the above reviews, few studies have specifically focused on a particular domain or area of green building research. Such as some studies highlight the benefits of green building (e.g., ), few focused on exploring the drivers of green building (e.g., Darko, Zhang, & Chan, 2017;Ahn, et al, 2013), some specifically discusses the barriers or risks of green building (e.g., Nguyen & Macchion, 2022;Chan et al, 2018;Nguyen, 2017;, project delivery outcomes e.g., (Ahmad, & Aibinu, 2017;Korkmaz, Horman, & Riley, 2009)), and few suggests some critical success factors (e.g., Chen, et al, 2022;Gunduz, & Almuajebh, 2020;Sfakianaki, 2018) and some highlight the strategies to overcome the barriers (e.g., Sabbagh et al, 2019;Teng, et al, 2016;Hoffman & Henn, 2008). Balabel and Alwetaishi (2021) compared green buildings with traditional construction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above reviews, few studies have specifically focused on a particular domain or area of green building research. Such as some studies highlight the benefits of green building (e.g., ), few focused on exploring the drivers of green building (e.g., Darko, Zhang, & Chan, 2017;Ahn, et al, 2013), some specifically discusses the barriers or risks of green building (e.g., Nguyen & Macchion, 2022;Chan et al, 2018;Nguyen, 2017;, project delivery outcomes e.g., (Ahmad, & Aibinu, 2017;Korkmaz, Horman, & Riley, 2009)), and few suggests some critical success factors (e.g., Chen, et al, 2022;Gunduz, & Almuajebh, 2020;Sfakianaki, 2018) and some highlight the strategies to overcome the barriers (e.g., Sabbagh et al, 2019;Teng, et al, 2016;Hoffman & Henn, 2008). Balabel and Alwetaishi (2021) compared green buildings with traditional construction.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, a number of studies have attempted to investigate the risk factors in implementing GB projects in recent years (Nguyen and Macchion, 2022). However, the identification and classification of GB risks remain inconsistent in previous studies (Nguyen et al, 2021).…”
Section: Theoretical Background 21 Risks In Gb Projectsmentioning
confidence: 99%
“…This section provides an overview of GB risk studies to position this research within the existing literature. The results of the literature review indicated that a growing number of studies had investigated risk in GBs in recent years (Nguyen and Macchion, 2022).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations